Martienssen, Rex Distin Repertory theatre working drawing. 1928 Final year student design project. Front elevation - Martienssen, Rex Distin (My University, 2011)
Martienssen, Rex Distin. Repertory theatre working drawing. 1928 final year student design project. Front elevation
Ink on canvas.
Keywords: Martienssen, Rex Distin. Repertory theatre. Working drawing. 1928. Front elevation